Bilateral spontaneous hyphaema in juvenile xanthogranuloma - Vijayalakshmi P (Indian Journal of Ophthalmology, 2006)
This report describes a rare occurrence of bilateral, spontaneous, nontraumatic hyphema in a 6 weeks old infant, associated with a small, multiple skin lesions. The diagnosis of juvenile xanthogranuloma was confirmed by histopathological examination of the cutaneous lesions. The hyphaema cleared gradually in 2 weeks time with conservative management.